MSMEs CAPACITY BUILDING THROUGH DIGITAL LITERACY IN BUMDES MSMEsIN THE DISTRICT OF ROAD CAGAK SUBANG REGENCY - Rasman Sonjaya; Almadina Rakmaniar; Irma Purnama Sari; Ahmad Fahrul; Muchtar Muchtar; Nur’aeni Nur’aeni (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The Covid-19 pandemic has had an extraordinary impact on business continuity, including Micro, Small and Medium Enterprises (MSMEs). The majority of MSMEs have been negatively affected by the Covid-19 pandemic. The digitization of MSMEs is an effort to change from conventional to digital systems as an effort to increase the effectiveness and efficiency of MSME business and operational processes. The digitization of MSMEs has made MSME business actors change their business management from conventional to modern practices. However, there are still many people who do not understand that the use of digital media is an obstacle for various aspects, one of which is MSME actors in Jalan Cagak District, Subang Regency. The opportunity to be able to introduce MSME products is very open with digital media. This should be able to help and boost the economy of MSMEs in Jalan Cagak District, Subang Regency, by taking advantage of various opportunities as creative content industry players.The problems that have been identified are the things that are discussed together by the PKM team (community activity program), in order to be given the best solution, the problem is how the current content creators become qualified so that they can help in efforts to increase digital media literacy. In this PKM activity, the team will carry out activities based onseveral methods. The expected output target in this activity is so that digital media literacy can be in demand with quality creative content.The approach method used to overcome problems faced by partners is through outreach, training or counseling and consulting activities. Then an active participatory approach is carried out between the proposing team and partners on an ongoing basis and plays an active role in providing assistance and coaching in the creation of digital creative content.